Enteric and feces methane emissions, fermentative ruminal parameters and feeding behavior of cattle fed cottonseed and vitamin E - Nogueira, Ricardo Galbiatti Sandoval (2017)
Problems about greenhouse gas emissions attributed to cattle production and improvements in the productivity of these animals has been growing and becoming increasingly important. Cattle releases methane as part of their digestive process, and this represents loss of energy for the animal. The decomposition of feces releases methane and it can be recovered by digester and transformed into different types of energy. Thus, aiming to quantify the potential production of enteric methane and anaerobic fecal decomposition, as well as to evaluate ruminal and behavioral parameters of cattle fed with cottonseed and vitamin E. Six cannulated cows (864±16 kg) were distributed in a replicate 3x3 Latin square. Treatments were: 1) control diet; 2) CS: basal diet plus 30% cottonseed and 3) CSVitE: basal diet plus 30% of cottonseed plus 500 UI of vitamin E. Results were compared through orthogonal contrast and values were considered significant when P0,05. No differences were observed for dry matter intake (DMI), as well as digestibility of DM and neutral detergent fiber (NDF). Animals supplemented with cottonseed spent more time eating and ruminating and less time in idles. Reduction in the concentration and production of acetate, butyrate and the acetate: propionate ratio was observed in animals fed cottonseed compared to the control. Enteric methane mitigation was observed for the cottonseed treatments compared to the control. Changes in the substrates characteristics used to load the digesters were observed. However, no differences were verified for the total biogas production, methane yield and capacity to recover the energy of the feces in the form of methane. Inclusion of 30% cottonseed can be used as a strategy to mitigate enteric methane, without causing losses in the DMI, nutrients digestibility and anaerobic digestion of feces. In addition, it promoted favorable changes in the ingestive behavior, ruminal fermentation products, as well as in the energy partition of the gastrointestinal tract. Vitamin E when is used as antioxidant had not effect on ruminal fermentation, feeding behavior and feces anaerobic digestion, thus the inclusion is not advised due absence of positive results.